Kebijakan Hukum Pidana Dibidang Transaksi Elektronik Sebagai Tindak Pidana Non-Konvensional - Melani, Melani; Disemadi, Hari Sutra; Jaya, Nyoman Serikat Putra (Universitas Negeri Semarang, 2020)
The development and progress of electronic transactions has resulted in changes in the activities of human life in various fields which have directly given rise to new forms of legal action that require Indonesia to form arrangements regarding electronic transaction management. The purpose of this study is to find out the background of the birth of criminal law policies regarding electronic transactions and to find out the formulation of criminal acts regarding electronic transactions in Law Number 19 of 2019 concerning Information and Electronic Transactions. The results of this study indicate that the background of the birth of the criminal law policy in the field of electronic transactions is the development of crime through electronic systems in society. Although crime through an electronic system is virtual, it can be categorized as a real legal act or action. Juridically, legal actions in this cyber space are regulated in the ITE Law. This ITE Law is an absolute legal approach to safeguard security in cyberspace and produce legal certainty on technology utilization issues.